Roblib: An educational program for robotics - Ferreira, N. M. Fonseca (2019)
The paper presents a program for robotics education that runs on standard PC's under the Microsoft environment. The RobLib package is designed for undergraduate students and emphasis the fundamental aspects of robot modelling and control. The software is self-explanatory and uses menus, dialog boxes with figures and context-dependent on-line help. In this perspective, students are motivated to investigate on the workspace, kinematics, dynamics, trajectory planning, position and for control of manipulators. Based on this first experience, further studies on robotics, using more sophisticated packages and concepts, are, then, more attractive from the students point of view.